Active Compounds and Antibacterial Activity of Banana (Musa paradisiaca) var. Agung Bunches and Combs Extracts Against Escherichia coli Analysis - Ade Wahyu Pratama; Utami Sri Hastuti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Escherichia coli cause diarrhea. E. coli infections can be treated using synthetic antibiotics. Natural antibiotics are an alternative for prevent E. coli infections as synthetyc antibiotic substitute. Natural antibiotics are come from plants part such as agung banana’s (Musa paradisiaca) bunch and combs. This bananas are used as a dessert fruits. The waste of this friut, such as bunches and fruit comb. This banana plant is potentially as antibacterial substance. The aims of this research are, 1) to examine the antibacterial effect of banana bunch and comb extracts; 2) to determine the effective concentration of the extract against the E.coli growth; and 3) to analysis of the active compounds content of banana bunch and comb extracts. Methodology: The antibacterial effect was examine using the agar well diffusion. Total active compound levels was examine using the UV-Vis spectrophotometry method and the derivative compounds uses the LCMS method. Findings: The research results showed the bunches had antibacterial effect against E. coli and the effective concentration is 90% with the highest inhibitory zone size diameter is 6.98 ± 0,00 mm, while the combs effective concentration is 80% is 6.55 ± 0.81 mm. The antibacterial effect of both extracts is moderate categorize. The highest content of active compounds in the bunches is phenol, with content: 70.70 mg/g and in the comb is 45.82 mg/g. Contribution: This research contributes to the utilisation of organic waste as an alternative source of environmentally friendly natural antibacterial agents and supports innovation in phytopharmaceuticals based on local plants.